Self-Control dan Cyberslacking Pada Mahasiswa - Maria Chrisnatalia; Dhiaviola Leoniharza; Stephanus Benedictus Bera Liwun (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
The learning process is frequently carried out using the internet, as a tool for supporting the academic activities. Self-control in internet usage is the required characteristic for student in the student-centered learning activities. However, there is a behavior called cyberslacking, or using the internet during the work time for non-work purposes (or in this context, for non-study purposes) that must be avoided because it can affect the learning outcomes and concentration during the study. The purpose of this research is to examine the effects of self control and cyber slacking to students. This study used a quantitative method, with 157 internet- active users students served as the research sample/ subjects. The cyberslacking activities were measured with by Akbulut scales, and the self control ability were measured with the Tangney scales. The sampling technique used purposive sampling and regression analysis techniques. The results showed that there was 32.2% of self-control affecting the cyberslacking behavior among students. The non-study purposes were for sharing information and shopping, that hit high score, where the male and female students had high categories in the same element. Based on the hypothesis testing results, this study's hypothesis is accepted.